Assessment Keberlanjutan Perikanan Tangkap Menggunakan Analisis Multi Indikator di Sungai Katingan, Kalimantan Tengah - Bambang Sulistiyarto (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2018)
This study aims to conduct an assessment of the capture fisheries sustainability in the river using multi-indicator analysis with the study area in the Katingan River, Kamipang District, Katingan Regency, Central Kalimantan. The parameters of the capture fisheries sustainability indicators studied include ecological parameters, fishing activities, and socio-economic of fishermen communities. Ecological surveys were conducted to determine the condition of riparian plants, water quality (dissolved oxygen, pH, turbidity), diversity of phytoplankton and macrobenthos. Information about fishing activities and socio-economic of fishermen communities were collected directly through interviewing fishermen with questionnaire assistance. 30 respondents were selected from all villages in Kamipang District. The sustainability status of capture fisheries is the combined value of all parameters assessed and weighted according to the important values of each parameter. The results showed that the capture fisheries sustainability in the Katingan River, Kamipang District was in a moderate condition with a score of 2.16 which means it was still sustainable but not in good condition. This study shows that the use of multi-indicator analysis for sustainability assessment of capture fisheries is able to provide an objective assessment of the inland fisheries, so that they can be used as a reference for management policy. Keywords : Katingan River, inland fisheries, sustainability indicator, multi-indicator, limited data.